Characterization, modelling and purification of a Molybdenum-reducing enzyme from a seawater-tolerant Bacterium - Abdul Rahman, Mohd Fadhil (2018)
Molybdenum, which is an emerging pollutant is toxic to spermatogenesis in several animal model and to ruminants. In Malaysia, the source of molybdenum pollution is from the dumping sites of waste oil lubricant. Molybdenum can be reduced to molybdenum blue by bacteria and form the basis for bioremediation of molybdenum. A novel seawater-tolerant Mo-reducing bacterium has been isolated from Pantai Merchang, Terengganu 1. The bacterium was identified by molecular phylogenetic analysis as Kluyvera sp. strain UPM-FR1. The optimum conditions for Mo reduction by using One-Factor-at-a-Time (OFAT) method showed that sucrose at between 30 and 50 g/L was the best carbon source. Ammonium sulphate at 10 g/L was the best nitrogen source. The optimal initial pH and temperature were pH 6.0 and from 27 to 35°C, respectively. The optimum phosphate concentration was 2 mM and the optimum molybdate concentration was 10 mM. The Mo-reducing capacity was strongly inhibited by the heavy metal mercury, followed by copper, silver and chromium. Optimization of Mo-reduction through Response Surface Method (RSM) begins with a pre-screening Plackett–Burman method which showed that molybdate (A), phosphate (B), pH (C), incubation time (G), and pH and phosphate (BC) were the significant (P<0.05) parameters influencing Mo-blue production. Surface plots show the optimum concentration of molybdate and phosphate occurred at 30 mM and 3.95 mM, respectively, while the optimum concentrations of molybdate concentration and pH occurred at 30 mM and 6.8, respectively. Surface plots also indicated that the optimum concentrations of molybdate concentration and time occurred at 30 mM and 36 h, respectively while the optimum concentrations of phosphate concentration and pH occurred at 3.95 mM and 6.25, respectively. The best solution satisfying the optimality goal was molybdenum at 34.89 mM, phosphate 4.04 mM, pH 6.81 and incubation time of 34.92 h, with the overall Mo-blue production of 12.6 compared to OFAT at 6.7 absorbance value. Modelling studies showed that the best primary model was modified Logistics model, while secondary modelling showed that the Luong model was the best with the calculated value for the Luong’s constants, which were qmax, Ks, Sm, and n that were 2.22±5 mole Mo-blue hr-1, 23.14±7.45 mM, 70.34±1.67 mM and 1.34±2.21, respectively. On the other hand, the best kinetic model for the effect of molybdate on molybdenum bioremoval rate using the dialysis tubing method was the Yano model. The calculated value for the Yano’s constants, which are qmax, Ks, Ki, and n were 2.454 ±2.12 mole Mo-blue hr-1, 24.18±4.23 mM, 87.82±8.19 mM and 0.258±0.121, respectively. Prior to the purification of the Mo-reducing enzyme, initial experiments shows that the Mo-reducing enzyme was stable in between pH 7 and 7.5. Both DTT and -mercaptoethanol are capable to restore the Mo-reducing enzyme activity. The results also show that none of the metabolic inhibitors inhibited the Mo-reducing enzyme from this bacterium suggesting that the electron transport system is not the site of Mo reduction to Mo-blue. The crude enzyme extract was fractionated with ammonium sulphate (40-50% fraction) and gel filtration on GF-250 yielding a 19.8 fold purification. The Mo-reducing enzyme is estimated to be at 100 kDa. The purified enzyme shows a maximum activity at pH 5.5 and a maximum activity in between 30 and 35oC. The Vmax for NADH and NADPH were at 8.6±0.25 (± standard error value) and 8.01±0.51 nmole Mo blue/min/mg protein, respectively. The apparent Km for NADH and NADPH were 1.55±0.16 mM and 4.15±0.64, respectively. The Vmax and Km for LPPM were 8.755±0.26 nmole Mo blue/min/mg protein and 3.37±0.35 mM, respectively. To conclude, all of the objectives in this thesis have been accomplished and a novel Mo-reducing bacterium with a novel seawater tolerant capacity had been isolated and characterized. This bacterium will be very useful in remediating molybdenum pollution in the coastal areas or in seawater using the dialysis tubing as an entrapment tool.